Adjunctive Use of the Dermocartilaginous Ligament for Dorsal Irregularities in Primary Rhinoplasty. Issue 6 (September 2018) - Ozturan, Orhan; Yenigun, Alper; Tugrul, Selahattin; Aksoy, Fadlullah
Abstract : Abstract: Nasal dorsal irregularity is a common postrhinoplasty complication in spite of meticulous smoothing. Utilization of the dermocartilaginous ligament in 2 different fashions for different purposes was described before. A novel utilization of the dermocartilaginous ligament as a flattened and pedicled flap from the cephalic attachment for nasal dorsal irregularities was presented in this article. This surgical technique was applied in 11 cases. Eight of them had thin skin, 2 had skin with medium thickness, and 1 had thick skin. They were followed on an average for 27 months (between 6 and 37 months). All of the patients had satisfactory esthetic results, and there was no apparent irregularities observed over the nasal dorsum. No complications such as infection or hematoma occurred during the early or late follow-up periods. Instead of discarding the dermocartilaginous ligament, it can be used adjunctively to conceal the nasal dorsal irregularities to attain a smoother dorsal nasal surface by increasing soft tissue cushion over the osseocartilaginous dorsum. Transposing of the dermocartilaginous ligament also relieves dynamic drooping of the nasal tip, shortening of the upper lip, and undesirable gingival display.